2015
DOI: 10.1016/j.matdes.2015.07.071
|View full text |Cite
|
Sign up to set email alerts
|

A review of friction stir welding of aluminium matrix composites

Abstract: As a solid state joining process, friction stir welding (FSW) has proven to be a promising approach for joining aluminium matrix composites (AMCs). However, challenges still remain in using FSW to join AMCs even with considerable progress having been made in recent years. This review paper provides an overview of the state-of-the-art of FSW of AMC materials. Specific attention and critical assessment have been given to: (a) the macrostructure and microstructure of AMC joints, (b) the evaluation of mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(114 citation statements)
references
References 62 publications
9
104
0
1
Order By: Relevance
“…The Tensile strength is found to be increased with increasing the rotational speed up to specified limit for AA6351 Al alloys as reported by [ 5 ].The tensile properties and fracture locations have been investigated by many authors [ 6,7,8 ] they are fabricated metal sheets alloy using FSP. The results are revealed that the rotational speed has a significant influence on the tensile strength as a result of improving grain refinement of the material.…”
Section: Introduction:-mentioning
confidence: 76%
“…The Tensile strength is found to be increased with increasing the rotational speed up to specified limit for AA6351 Al alloys as reported by [ 5 ].The tensile properties and fracture locations have been investigated by many authors [ 6,7,8 ] they are fabricated metal sheets alloy using FSP. The results are revealed that the rotational speed has a significant influence on the tensile strength as a result of improving grain refinement of the material.…”
Section: Introduction:-mentioning
confidence: 76%
“…Some studies have demonstrated the effect of grain size on the mechanical properties of FSW welds [41,51,52,55], in which more refined grains obtained in SZ lead to an increase of hardness. However, Salih et al found that the micro-hardness in the nuggets (with the lowest grain size) is lower than that in base material [17], which is in disagreement with the Hall-Petch relationship. It is very possible that distribution of hardening phases exerts a significant influence on the micro-hardness.…”
Section: Microhardnessmentioning
confidence: 95%
“…Avettand-Fènoël et al [16] discussed the FSW of metal matrix composites in detail. Salih et al [17] gave an overview of the FSW of aluminium matrix composites. Thomas et al [18], Rai and Bhadeshia [19], and Zhang et al [20] comprehensively reviewed the FSW tools of aluminium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Micro particles of reinforced particles precipitate on grain boundary and prevent grain growth hence fine grain structure. Homogenous dispersion of SiC particles in base metal and good bonding between SiC particles and base metal resulted in increase of ultimate tensile strength of composite material [5].…”
mentioning
confidence: 99%